Comprehensive care of a child suffering from cerebral palsy - Stecko, Monika Joanna; Wawryków, Agata; Korabiusz-Lewandowska, Katarzyna; Kordek, Agnieszka (Journal of Education, Health and Sport, 2020)
Cerebral palsy is a syndrome caused by the damage of central nervous system in the early period of its development [1]. In cerebral palsy, motor disorders are associated by symptoms, being also a result of brain damage. Rehabilitation of children suffering from developmental disorders should be early, comprehensive and continuous. Child suffering from cerebral palsy should work with a team of physicians, therapists, that is, physiotherapist, psychologist, educator and other specialists adapted individually to the needs of a patient.